Basketball - Sampaio, J.; Goncalves, B.; Mateus, N.; Shaoliang, Z.; Leite, N. (Modelling and simulation in sport and exercise, 2020)
The studies focused on positional-derived variables in basketball are still very limited to small samples. Usually, box-score statistics are used for explaining the game dynamics and outcome in basketball and therefore lead to the problems that are discussed in Part III. As in soccer and handball, however, position data of the players and the ball become increasingly important in basketball: Player-tracking technology is one of the most recent technological advances in basketball. Powerful Computer vision Systems were designed with fine-tuned algorithms capable of tracking with relatively high accuracy the players` positioning and, subsequently, all derived variables such as distance covered and speed.